On Trying to Leave Truth Alone. Issue 1 (9th February 2021) - Zapero, David
Abstract: According to a certain conception of language, any sentence can, when used on an occasion, have any of indefinitely many truth-conditions. Such a conception of language gives us reason to think that the question of whether the notion of truth has a distinctive content cannot be settled by looking solely at the predication of truth. By focusing on the predicate 'true' when trying to determine the significance of the notion of truth, we may have been looking in the wrong place.